ENHANCING MOLD DESIGN FOR UNIFORM PREFABRICATED BUILDING CONSTRUCTION - Fischer, Martin (Ayden International Journal of Basic and Applied Sciences, 2024)
In the field of construction industrialization, the design and manufacturing of molds for prefabricated components have become a critical aspect. However, several challenges plague this industry, including issues like unreasonable structure, rusting, and low standardization. To address these problems, this paper proposes a design control model for prefabricated building components using Quality Function Deployment (QFD) and Design Structure Matrix (DSM) methods. By applying QFD, we systematically analyze the relationships between various control elements that impact the design of prefabricated components. These elements are evaluated in terms of prefabricated building requirements, functional structures, and specialized design. Furthermore, we delve into the information flow between different design elements and construct a DSM matrix, which helps uncover potential rework effects between these elements